Pengaruh Penggunaan Media Audio Visual Terhadap Keterampilan Smash Bulutangkis - Akbaruddin, Asep; Arby, Kurniawan (STKIP Pasundan, 2020)
The purpose of this study was to determine the effect of using audio visual media on smash skills in learning badminton at SMP Negeri 2 Dayeuhkolot. The method used in this study was an experimental method with a one shoot case study research design. The population in this study were all students of IX’s class who participated in learning sports education at SMP Negeri 2 Dayeuhkolot of Bandung Regency, amounting to 395 people and the samples of this study were 40 students of IX-J’s class. The instrument used in this research is a smash skill test in badminton. The data processing and analysis techniques used the SPSS 23 program. The results of the research showed that the average score of the students was 19.20 which means that the effect of learning audio-visual media on badminton smash skills is good. With a percentage of 35% is sufficient, 57.50% is good and 7.5% is very good. From the research results it is known that the use of audio-visual media has a good effect on badminton smash skills with a percentage of 57.5%.